(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
With the rapid growth and popularity of Facebook among students in higher education, the aim of this study is to explore the usage purposes among students including their academic and non-academic usage purposes in relation to gender, background, study level, and the length of their experience using Facebook. For this purpose, 105 local and international students were surveyed at a large public technology university in Malaysia. The results revealed that academic usage was limited compared to other usage purposes, such as social interaction, news, and entertainment. In relation to the academic usage, the results revealed that that study level and academic usage of Facebook were significantly related, while no significant relations were found in relation to gender, background or experience.